Does Working-From-Home Work? A Multidimensional Investigation of the Effect of Workspace Environment on Self-Control - Austin, Tess (Auckland University of Technology, 2024)
This research report aimed to investigate whether workspace environment, specifically working-from-home versus working at a company-owned premises, affects the self-control of employees. Firstly, self-control has been measured in many ways in past research. However, by examining the literature it was discovered that utilising both state and actual measures of self-control would provide a comprehensive measurement of self-controlled behaviour in employees. Previous research has indicated contrasting evidence to the affect workspace environment may have on self-control. Some research states that increased privacy and control in a WFH environment may increase self-control. Other research, such as the process and ego-depletion models of self-control, provide evidence which indicates that increased visual distractions in a WFH environment will decrease self-control in employees. The present study used response inhibition, behavioural and trait measurements of self-control in a sample of employees who worked in different spaces. Analysis did not find a difference in self-control on any measure between different workspaces. This finding may be due to mediating factors, such as privacy, control and perceived isolation which were not controlled for in the present study. However, some interesting correlational findings exist. Correlations existed between response inhibition and behavioural measures of self-control; however, the trait measure did not correlate and provided a low reliability score. This may indicate that this measure should be modified in future uses. Correlations were also discovered for self-control measures and sleep, age and motivation. This adds evidence to past research which indicates these factors influence performance on self-control tasks. Overall, more research is needed to determine the effect of workspace environment on employee's self-control.